An experimental investigation on time response characteristics of SMA wire actuators under electric heating for engineering design. (31st August 2020) - Guan, Jing-Han; Pei, Yong-Chen; Wang, Shun
Abstract: Shape memory alloys (SMAs) are proved to have high energy-to-volume ratio and large displacement. However, they have the defect of longer recovery time. In practice, designing SMA wire actuators is a very complex and exhausted thing because of extensive and various needs. In this study, a special setup was designed, which can test many characteristics of a SMA wire heated by electric current, including temperature, deformation, response time, recovery time, wind speed (for cooling), and load. Besides, an empirical model of the wires temperature was presented for avoiding overheating the wires. By fitting experiment data, unknown parameters in this model are determined. Next, main design parameters are investigated on how they exert effects on the characteristics of the SMA wires, including wire radius, convection type, load, and voltage. At last, the time response characteristics were also analyzed. Through this study, one can make clear how each design parameter plays its part in SMA wire actuators.